Quality of Higher Education and the Labor Market in Developing Countries: Evidence from an Education Reform in Senegal - Dorothée Boccanfuso; Alexandre Larouche; Mircea Trandafir (Institute for the Study of Labor (IZA), 2015)
While many studies examine the effect of primary education quality on labor market outcomes in developing countries, little is known about the effects at higher levels. We exploit the quasi-experiment provided by a large-scale education reform launched in Senegal in 2000 to investigate how quality improvements at the university level affect employment. Our difference-in-difference estimates suggest that young high-skilled workers experienced a nine percentage-point employment gain relative to older workers. They are also more likely to have "better" jobs (in the service industry or government), suggesting a reduction in the mismatch between the quality of high-skill labor demanded and supplied.
Keywords: I21; O15; O55; 330; higher education; employment; impact analysis; quality mismatch